If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1) = y + 3 Multiply 4 * 1 4 = y + 3 Reorder the terms: 4 = 3 + y Solving 4 = 3 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 4 + -1y = 3 + y + -1y Combine like terms: y + -1y = 0 4 + -1y = 3 + 0 4 + -1y = 3 Add '-4' to each side of the equation. 4 + -4 + -1y = 3 + -4 Combine like terms: 4 + -4 = 0 0 + -1y = 3 + -4 -1y = 3 + -4 Combine like terms: 3 + -4 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1
| (2x+6)+(3x+2)=0.5 | | 6(-8r-2)= | | 4(-1)=y+3 | | 74-b=19 | | 65=z+19 | | 3q=27 | | 3-c=14 | | 62=71-s | | 9x=2y+23 | | -5(a)+7=43 | | -3n-6=n-4 | | 62=71-2 | | n^(1/3)-6=0 | | 3x(x-2)-3(x-2)(x+2)=(x+1)(x+2) | | p-8/5=5p-8/4 | | log(8x+8)=2 | | 7-5(a)=43 | | 35/t=5 | | 4(6b+8)=2(11b+30) | | r+14=58 | | 64=90-f | | 129=41+e | | 9u=54 | | a+5=-10a+5 | | 38=t-13 | | 30w+200=20w+450 | | 2^3•4^3•5/5^2•2^4 | | (t+6)(t-6)=-16t | | -18-6k=6(7+9k) | | 113=31+a | | 8-3=4(4f-8) | | 24+2x=10x+4+2x |